2008
DOI: 10.2217/14622416.9.7.847
|View full text |Cite
|
Sign up to set email alerts
|

Global Pharmacogenetics: Genetic Substructure of Eurasian Populations and its Effect on Variants of Drug-Metabolizing Enzymes

Abstract: Although the tested variants were present in the neighboring, yet secluded, populations at the expected range of frequencies, the observed frequencies were significantly variable across Eurasian populations, indicating potential relevance to clinical decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 70 publications
3
25
0
7
Order By: Relevance
“…However, compared with the CYP2E1*6 allele frequency in the Caucasian population (11.4%), significant differences were observed in the mainland Chinese Han (26.2%, Po0.01) and Chinese Uygur (18.8%, Po0.05) populations, but no significant difference was observed in the Chinese Kazakh population (14.5%), leading to speculation that this discrepancy might be due to the ethnic complexity of this Eurasian admixed population. The present results support the proposition that the P450 genetic distances were well correlated with the geographic distances across Eurasian populations, 17 and indicate potential relevance to clinical decision making.…”
Section: Resultssupporting
confidence: 87%
“…However, compared with the CYP2E1*6 allele frequency in the Caucasian population (11.4%), significant differences were observed in the mainland Chinese Han (26.2%, Po0.01) and Chinese Uygur (18.8%, Po0.05) populations, but no significant difference was observed in the Chinese Kazakh population (14.5%), leading to speculation that this discrepancy might be due to the ethnic complexity of this Eurasian admixed population. The present results support the proposition that the P450 genetic distances were well correlated with the geographic distances across Eurasian populations, 17 and indicate potential relevance to clinical decision making.…”
Section: Resultssupporting
confidence: 87%
“…Most Caucasians expressed the CYP3A5 6986GG genotype associated with a small amount of translated CYP3A5 protein, with a G allele frequency ranging from 0.87 to 0.94 in various Caucasian populations (22,29). In contrast, in various Asian populations, G allele frequencies were lower, ranging from 0.59 in Indians to 0.65 in Cambodians, as demonstrated in this study, 0.67 in a Vietnamese population, and 0.74 to 0.78 in Japanese, Chinese, and Korean populations (23,29). The frequency is even lower in patients of African descent (0.36) (22).…”
Section: Discussionmentioning
confidence: 99%
“…The frequencies of defective CYP2C9 alleles (CYP2C9*2 and CYP2C9*3) are higher in Caucasians (18.9%) than in Asians (2.5-3.5%) [11,12]. Conversely, the frequencies of defective CYP2C19 alleles (CYP2C19*2 and CYP2C19*3) are higher in Asians (33-43.5%) compared to Caucasians (13.6%) [11][12][13]. Population studies have shown that individuals can be classified into three subgroups: namely, homozygous extensive metabolizers (homo EMs), heterozygous EMs (hetero EMs) and poor metabolizers (PMs) according to the number (i.e.…”
Section: Cyp Polymorphisms and Aed Therapymentioning
confidence: 99%